Pré-melhoramento de feijões crioulos e comerciais cultivados no Estado do Espírito Santo - Carvalho, Marina Santos (2019)
The common bean (Phaseolus vulgaris L.) is a legume of the Fabaceae family, being an important source of proteins and fibers. The landrace type is cultivated mainly in family agriculture and deserve prominence for having genes of interest for breeding. In the state of Espirito Santo, production is predominantly carried out through family farms in properties distributed in all regions of the state. The common bean landraces are adapted to local conditions and selected over several generations, however they are not characterized. In order to identify potential common bean landrace and commercial for use in breeding, the objective of this study is to characterize by means of molecular markers SSRs (Single Sequence Repeat), SNPs (Single Nucleotide Polymorphism) and by agromorphological descriptors the genetic diversity of a collection of beans grown in the state of Espírito Santo in comparison to commercial cultivars obtained from several breeding programs. Initially, 159 accessions of landraces beans were harvested on public farms and public markets in the state of Espirito Santo and 27 commercial cultivars were transferred from the work collection of the Capixaba Institute for Research, Technical Assistance and Rural Extension (Incaper). These accessions were evaluated for genetic diversity with 13 microsatellite loci. The mean polymorphic information content of the SSRs was 4.46, characterizing them as moderately informative and the expected heterosygosity (He) was 0.51, suggesting that the accesses have a wide genetic diversity. The allelic number (A), private (AP) and rare alleles (AR) were observed in greater magnitude in the bean landraces (landraces, He = 0.50, A = 5, AP = 29.30, commercial, He = 0.42, A = 2.92, AP = 2, AR = 8), demonstrating that the common bean landraces potentially represent a reservoir of rare and private alleles compared to commercial stocks. The analysis of molecular variance showed significant genetic diversity and moderate differentiation between the groups of commercial and criollo accesses (9.89%, FST = 0.074, P <0.01) and within the group was 90.11%, but not significant. The UPGMA divided the accesses into 10 main groups, of which one was formed by 89% of the accesses (138 lndraces and all the commercial ones), which was subdivided into 28. The UPGMA allowed to discriminate the IX 50 accesses that represented a subset of common bean divergent. These accesses were submitted to three field experiments in two harvests in the agricultural years of 2017 and 2018, conducted in randomized blocks with three replicates. Twelve morphoagronomic variables were analyzed. The multivariate analysis of the variance indicated significant differences among the common bean accesses evaluated, suggesting there is variability among accessions. The characteristic with greater discriminatory power was the height of plants ranging from 30.89 (Red-132) to 102.29 cm (Pearl-22). The accessions Green-111, White110, Pearl-102, Black 13-69, Beans queen-18, White-05 showed high levels of productivity (above 3,000 kg.ha-1). Six groups were formed by the UPGMA, one of them composed of 96.30% of the commercial cultivars, suggesting that the landraces have characteristics of interest, since the commercial ones have already undergone some process of genetic improvement. Later, there was an increase in the bean collection with other samples collected in the state, totaling 206 landraces accesses, as well as 47 samples of commercial cultivars provided by Embrapa Rice and Bean and 12 by Incaper. These samples were analyzed with 23 SSR, labeled with fluorescence and analyzed in a multiplex coamplification system in capillary electrophoresis and by 251 SNPs. In the total collection the SSR markers allowed the detection of 272 alleles, with an average of 10.74 per locus. For the SNPs the total number of alleles was 439 with a mean of two per locus. SSR produced high PIC values (0.65) while SNPs had a lower PIC value (0.27). The mean genetic diversity, quantified by the expected heterozygosity was higher for the SSR loci (0.678) than for the SNPs (0.34). The ideal number of groups by the STRUCTURE software analysis were two for both markers. Genetic dissimilarity matrices for allelic data from SSRs and SNPs were highly correlated (r = 0.74, 0.005), so the markers were combined and analyzed for understanding the genetic relationships among the studied subjects. The neighbor joining analysis, considering the simple coincidence genetic distance, grouped the 265 accessions into 17 subgroups. This work revealed a wide genetic divergence in the work collection, which makes it a valuable source for the conservation, management and later use of the accesses in crop breeding programs